2015
DOI: 10.1093/cercor/bhv086
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Neural Signatures of Basic Emotions

Abstract: Categorical models of emotions posit neurally and physiologically distinct human basic emotions. We tested this assumption by using multivariate pattern analysis (MVPA) to classify brain activity patterns of 6 basic emotions (disgust, fear, happiness, sadness, anger, and surprise) in 3 experiments. Emotions were induced with short movies or mental imagery during functional magnetic resonance imaging. MVPA accurately classified emotions induced by both methods, and the classification generalized from one induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

40
313
5
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 357 publications
(394 citation statements)
references
References 72 publications
40
313
5
7
Order By: Relevance
“…Given recent evidence linking creativity to increased coordination/connectivity across DMN, CCN, and VAN (40), it is possible that hyperconnectivity while recalling a positive autobiographical memory is a substrate for greater propensity to creatively “think outside the box” (or beyond the task), which would be detrimental to affect regulation only to the extent that the content of such divergent thinking is less positive. Given that regions in our network do not serve unitary (e.g., exclusively negative or positive) emotional functions (41-43), the content resounding within an identical hyperconnected network might therefore differ in healthy individuals, e.g., being full of pleasant, fulfilling memories.…”
Section: Discussionmentioning
confidence: 99%
“…Given recent evidence linking creativity to increased coordination/connectivity across DMN, CCN, and VAN (40), it is possible that hyperconnectivity while recalling a positive autobiographical memory is a substrate for greater propensity to creatively “think outside the box” (or beyond the task), which would be detrimental to affect regulation only to the extent that the content of such divergent thinking is less positive. Given that regions in our network do not serve unitary (e.g., exclusively negative or positive) emotional functions (41-43), the content resounding within an identical hyperconnected network might therefore differ in healthy individuals, e.g., being full of pleasant, fulfilling memories.…”
Section: Discussionmentioning
confidence: 99%
“…We found that different emotional experiences are often grounded in different distributed patterns, and that each distributed pattern reflects the interaction of domain-general processes. Much emphasis has been placed on distinguishing the neural patterns that distinguish one emotion category from another (e.g., Saarimäki et al, 2015;Tettamanti et al, 2012;Wager et al, 2015), but the domain-general emphasis specified in psychological construction suggests the potential for much more variability in emotional life (both within and between emotion categories; see, e.g., Wilson-Mendenhall et al, 2015;Wilson-Mendenhall et al, 2011). Because our findings are based on a composite dataset in which emotion category was a between-subjects manipulation, this study was not optimal for examining differences in the variety of emotional experiences.…”
Section: Discussionmentioning
confidence: 99%
“…These networks support more domain-general functions, such as executive function, affiliation, salience detection, and so forth, and thus contribute to constructing emotional experiences (as well as other kinds of experiences; Barrett & Satpute, 2013;. When regional or network patterns emerge for one emotion category versus another, this is because that category of emotional experiences tends to draw more on certain domain-general functions than others (Saarimäki et al, 2015;Tettamanti et al, 2012;Wager et al, 2015; WilsonMendenhall, Barrett, Simmons, & Barsalou, 2011). Consistent with meta-analytic evidence and other recent neuroscience findings, emerging psychological-construction approaches emphasize that a domain-general network approach is powerful because the interplay of networks could account for the wide variety of emotions that people experience in real life (e.g., Barrett, 2013;Wilson-Mendenhall et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the self-reported experience of various negative emotions is routinely related to poorer health, but the expression or suppression of emotions likely has quite different consequences for physiology, symptoms, and interpersonal relationships (Burns et al, 2008; Slavin-Spenny et al, 2013). Third, there is increasing recognition that each specific emotion has its unique triggers, appraisals, neural circuitry, and behavioral consequences (Barrett, 1998; Saarimäki et al, 2015). Thus, research on global states, such as depression or stress, is being complemented by studies of specific emotions such as fear, sadness, and anger (Inbar & Gilovich, 2011; So et al, 2015).…”
mentioning
confidence: 99%